EVALUASI PENGARUH SISTEM MANAJEMEN KESELAMATAN KERJA DAN KESEHATAN TERHADAP PT X - Margaretha, Farah; Utari, Leli (Fakultas Ekonomi, Universitas Negeri Jakarta, 2011)
Construction Industry is an industrial sector with high risk of work accident. Every year work accident at construction industry reached 32% from a whole work accident at Indonesia. Direct loss due to this accident can attain 300 billion every year. According ILO, Indonesia’s occupational safety rate in 2007 ranked at 52nd position out of 53 countries in the world that were surveyed by ILO. The objective of this research is to examine influence of Occupational Health and Safety Management System toward PT X performance’s as one of Contractor Company at Indonesia. Company’s performance that is examined is safety & health performance and competitiveness performance. Data in this research obtained from interview and questionnaire. These data then processed by using statistic descriptive method and Structural Equation Modeling (SEM) . The result then evaluated to observe Goodness of Fit (GOF) between model and data. The results from research shows that Occupational Health and Safety Management System influence safety & health performance and competitiveness performance significantly as indicated by result of the research that fulfill criteria of Goodness of Fit. Keywords: Occupational Health and Safety Management System, construction industry, corporate social responsibility